Bridelia ferruginea Promotes Reactive Oxygen Species Detoxification in N-Nitrosodiethylamine-Treated Rats. (1st September 2013) - Ajiboye, T. O.; Abdussalam, F. A.; Adeleye, A. O.; Iliasu, G. A.; Ariyo, F. A.; Adediran, Z. A.; Raji, K. O.; Raji, H. O.
ABSTRACT This study was aimed at investigating the in vitro and in vivo reactive oxygen species (ROS) scavenging and detoxification potentials of aqueous extract of Bridelia ferruginea (B. ferruginea). Reactive oxygen species scavenging potentials of the aqueous leaf extract of B. ferruginea (0.2–1.0 mg/ml) was investigated using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical, superoxide ion, hydrogen peroxide, hydroxyl radical, and ferric ion reducing system. The detoxification of ROS was evaluated in N-nitrosodiethylamine-induced redox imbalance in the liver of rats. B. ferruginea extract at 1.0 mg/ml scavenged the DPPH, superoxide ion, hydrogen peroxide, and hydroxyl radical at 87%, 83%, 92%, and 86%, respectively, it also reduced ferric ion significantly. ROS detoxifying enzymes (superoxide dismutase (SOD), catalase, glutathione peroxidase, glutathione reductase, and glucose 6-phosphate dehydrogenase) activities were significantly (p < .05) induced by B. ferruginea. These inductions significantly ( p < .05) attenuated the N-nitrosodiethylamine-mediated decrease in ROS detoxifying enzymes and compared favorably with Vitamin C. N-nitrosodiethylamine-mediated elevation in the concentrations of malondialdehyde, conjugated dienes, lipid hydroperoxides, protein carbonyl, and percentage DNA fragmentation were significantly (p < .05) lowered by B. ferruginea extract. Overall, the results of this study show that B. ferruginea leaf extract possess ROS scavenging and detoxification potentials.